Regulation/deregulation - Lim, Kean Fan (Wiley Blackwell, 2015)
Economic regulation is dynamically entwined with deregulation. Contrary to the logic of market fundamentalism, producers and/or consumers do not always benefit from deregulation. Rational-choice theories of regulation have not impacted economic-geographical research as much as Regulation Theory (RT). Developed in France to theorize the crisis of Fordism, RT underscores the importance of social regulation in the capital accumulation process. Rather than study deregulation as an endstate, RT emphasizes regulatory reconfiguration and repurposing. Despite its eventual decline, RT left a strong legacy on economic-geographical research on (de)regulation. There is strong potential for current and future studies to build on this legacy, particularly in research on variegated neoliberalization and primitive accumulation.